PENGARUH PROBABILITAS KEBANGKRUTAN, KOMPLEKSITAS OPERASI PERUSAHAAN, DAN INVESTMENT OPPORTUNITY SET TERHADAP AUDIT DELAY - Putrie Arlidjah Cita (2023)
This research aimed to examine the effect of bankruptcy probability, company operation complexity, and investment opportunity set on audit delay. The population in this study are trade, services, and investment companies listed on the Indonesia Stock Exchange in 2019-2021. The sample in this study obtained 151 companies which were selected by purposive sampling method. In this study, bankruptcy probability is measured by Springate, company operation complexity measured by dummy variable, and investment opportunity set is measured by gross book of property, plant, and equipment divided by gross book of total assets. Hypothesis test in this study used Panel Data Analysis using STATA 16 application with a significant level of 5% so the result of hypothesis test shows that bankrupcy probability have a negative effect on audit delay, meanwhile company operation complexity and investment opportunity set have no effect on audit delay. Keywords: Audit Delay, Bankruptcy Probability, Company Operation Complexity, Investment Opportunity Set.